Cognitive function in relation with bone mass and nutrition: cross-sectional association in postmenopausal women - Brownbill Rhonda A; Ilich Jasminka Z (BMC, 2004)
Abstract Background It has been suggested that bone loss and cognitive decline are co-occurring conditions, possibly due to their relationship with estrogen. Cognitive decline has been associated with various nutritional deficiencies as well. The purpose of this study was to determine if cognitive function is related to bone mineral density of various skeletal sites as well as to various dietary components. Methods Cross-sectional study with 97 healthy, Caucasian, postmenopausal women (59.4-85.0 years) enrolled in a larger longitudinal study, investigating the effects of sodium on bone mass. The subjects were divided into two groups based on cognition scores. Group 1 represented lower and Group 2 higher scores on cognitive function. Bone mineral density from the whole body, lumbar spine, femur and forearm were measured with the Lunar DPX-MD instrument. Anthropometry was measured by standard methods. Cognition was assessed using the Mini Mental State Examination. Cumulative (over 2 years) dietary intake from 3-day records was analyzed by Food Processor® (ESHA Research, Salem, OR) and cumulative physical activity was assessed using Allied Dunbar National Fitness Survey for older adults. Results Subjects' cognition scores ranged from 22-30 (normal, 27-30), indicating all subjects had either mild or no cognitive impairment. Multiple Analysis of Covariance adjusted for age, height, weight, physical activity, alcohol, calcium, sodium and energy intake, showed a statistically significant association between cognition and bone mineral density of all measurable sites (η2 = 0.21, P < 0.01). However, after Analysis of Covariance follow-up tests and Bonferroni correction, the differences for individual bone sites diminished, though Group 2 had higher adjusted means for all sites except for the femoral neck, Ward's triangle and trochanter. There was a positive significant association between cognition score and carbohydrate and potassium intake (η2 = 0.07, P = 0.050). Group 2 did have a significantly higher potassium intake (P = 0.023). In multiple regression, saturated fat had a significant negative relationship with cognitive function. Conclusions It appears mild degree of cognitive impairment may be a marker for lower bone mineral density as well as for a diet lower in carbohydrate and potassium intake, and higher in saturated fat. Consequently, older women with cognitive impairment may benefit of being screened for potential bone loss and poor nutrition.